Management accounting today: a perspective for tomorrow / Nikhil Chandra Shil, Mahfuzul Hoque and Mahmuda Akter - Shil, Nikhil Chandra; Hoque, Mahfuzul; Akter, Mahmuda (Faculty of Accountancy, 2014)
Management accounting practices greatly vary across different countries, even among firms operating within the same geographical boundary. Following the qualitative research methodology, this paper highlights selective management accounting practices by collecting and analysing data through in-depth interviews. With the exception of several interviewed firms, the findings of this study reflect the overall unpleasant status of management accounting practices in Bangladesh, which confirms the findings of previous studies. This paper also aims to address the causes of such poor status, reduce the gaps in the literature and pave a solid foundation for improving the management accounting practices in the country. This paper can serve as a reference on how a country moves toward improving its management accounting practices.